Intra-operative cortical motor mapping using subdural grid electrodes in children undergoing epilepsy surgery evaluation and comparison with the conventional extra-operative motor mapping. Issue 12 (December 2018) - Jain, Puneet; Whitney, Robyn; Strantzas, Samuel; McCoy, Blathnaid; Ochi, Ayako; Otsubo, Hiroshi; Snead, O. Carter; Weiss, Shelly; Donner, Elizabeth; Pang, Elizabeth; Sharma, Rohit; Viljoen, Amrita; et al.
Highlights: Extra-operative mapping (penfield technique) frequently leads to after-discharges and seizures. Intra-operative motor-mapping (IODCS-SDG) using "train of five" provided more mapping information. No stimulation-provoked seizures were noted during IODCS-SDG. Abstract: Objectives: The objective of this study was to review our experience with intra-operative "train of five" stimulation using subdural grid for motor mapping in children undergoing epilepsy surgery evaluation. Methods: Twenty consecutive children below 18-years of age with drug-refractory epilepsy who underwent invasive-EEG monitoring using subdural-grid placement and intra-operative motor mapping using direct cortical stimulation by sub-dural grid electrodes (IODCS-SDG) at our institution between January-2016 and June-2017 were reviewed. Stimulation was delivered through the subdural-grid electrodes using a train-of-five pulses and muscle responses were recorded by motor-evoked-potentials (MEPs). Intra-operative direct cortical stimulation delivered through a ball-tipped probe (IODCS-probe) and extra-operative motor-mapping (EODCS-SDG) were also performed. Results: IODCS-SDG was completed in 20 patients and subsequent EODCS-SDG was done in 17/20 patients. MEP responses were more commonly obtained in the deltoid (19/20), extensor-digitorum-communis (20/20) and first-dorsal-interosseus (19/20). The median thresholds varied between 40 V and 60 V for the six muscle groups. The respective IODCS-probe thresholds tended to be similar. No stimulation-provoked seizures or anaesthesia-related complications were noted during IODCS-SDG. EODCS-SDG could not be completed in 4/17 children and mapping data obtained was frequently inadequate. Nine patients demonstrated 100% concordance between IODCS-SDG and EODCS-SDG for the common mapped body regions. Stimulation-provoked seizures during EODCS-SDG were seen in 6/17 (35.3%) and after-discharges in 7/17 (41.2%) children. Conclusions: IODCS-SDG could be performed safely in children with drug refractory epilepsy undergoing invasive EEG monitoring. Significance: IODCS-SDG may be a useful adjunct to EODCS-SDG in motor mapping for children.